Advances in multicellular spheroids formation. Issue 127 (February 2017) - Cui, X.; Hartanto, Y.; Zhang, H.
Abstract : Three-dimensional multicellular spheroids (MCSs) have a complex architectural structure, dynamic cell–cell/cell–matrix interactions and bio-mimicking in vivo microenvironment. As a fundamental building block for tissue reconstruction, MCSs have emerged as a powerful tool to narrow down the gap between the in vitro and in vivo model. In this review paper, we discussed the structure and biology of MCSs and detailed fabricating methods. Among these methods, the approach in microfluidics with hydrogel support for MCS formation is promising because it allows essential cell–cell/cell–matrix interactions in a confined space.